PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN PENDAPATAN DAERAH KOTA TANGERANG SELATAN - Anandita Shakilah, Kezia; Prabowo, Budhi (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effest of employee work motivation and work environment on the performance of Regional Revenue Agency of Tangerang City both partially and simultaneously. The method used is the quantitative methhod. The sampling technique used is saturated sampling using a sample 100 respondents. Data analysis using validity test, reliability test, classical assumption test, regression anaysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The result of this study is that Work Motivation has a significant effect on employee performance with the regression equation Y = 8,324 + 0,821X1. Hypothesis test obtained t count > t table or (15.410 > 1.660). the work environment has a significant effect on emplovee performance with the regression equation Y = 15,148 + 0,667x2. Hypothesis test obtained value t count > t table or (9.720 > 1.660). Work Motivation and work emvironment have a significant effect on employee performance with the regression equation Y = 6,633 + 0,686X1 + 0,181X2. Hypothesis test obtained value F count > F table or (122.784 > 3.090). Thus H0 was rejected and H3 was accepted. This means that there is a significant influence simultaneously between work motivation and the work environment on employee performance.